Analysis of Challenges and Solutions to Students' Understanding of Mathematical Concepts in Algebra Material from Gender Perspective - Fionda Febrila Calista; Ahmad Fauzan; Armiati Armiati; Yulyanti Harisman (Newinera Publisher, 2026)
Algebra is one of the crucial topics in mathematics. However, many students struggle to master algebra concepts. If this is left unchecked, it will have a negative impact on the students' future. Students will have difficulty following mathematics lessons at higher levels, because algebra is the foundation of many advanced mathematical concepts. This research aims to conduct a case study on the understanding of mathematical concepts from a gender perspective and a literature review to determine the challenges and solution approaches to the understanding of mathematical concepts among middle school students in algebra. The methods applied are Systematic Literature Review (SLR) and case study research. The research results show that female students' understanding of algebra concepts is very good. Female students can explain examples and algebraic operations well and correctly. However, male students do not master the material well because they often make mistakes in algebraic operations. The main cause of the low understanding of algebra concepts among students is their inability to connect formulas and concepts with practical applications, lack of student engagement in the learning process, insufficient interactive learning media, and inadequate teaching methods. The proposed solutions are the use of more engaging and interactive media, the implementation of active and collaborative learning methods, and the utilization of technology in education.